Adsorption of β-Carotene in Isopropyl Alcohol with Decolorized Activated Carbon as Model for β-Carotene Adsorption in Crude Palm Oil - Maria Ulfah; Sri Raharjo; Pudji Hastuti; Purnama Darmadji (Indonesian Journal of Chemistry, 2017)
The objective of this research was to characterize the porosity of decolorized activated carbon (DAC) and its ability to adsorb β-carotene as a preliminary study to characterize activated carbon as an adsorbent to adsorb carotene from crude palm oil. The capability of DAC to adsorb β-carotene was studied using isopropyl alcohol as a solvent in equilibrium conditions. The adsorption time was specified for 0.5 to 60 min, while the DAC optimum concentration for adsorption of β-carotene was determined at a concentration of 0.5 to 2.5%. Adsorption isotherm study was conducted for a β-carotene concentration of 100 to 500 ppm and at temperatures of 30, 40 and 50 °C at equilibrium time and DAC optimum concentration. The results showed that the DAC had a surface area of 1068.391 m2/g, total pore volume of 0.952 cc/g, mesopore volume of 0.528 cc/g (55.4%) and mesopore radius of 15.26 Å. Based on the levels of β-carotene adsorbed onto the DAC, the equilibrium was reached after adsorption of 5 min. Decolorized activated carbon with a concentration of 1.5% was able to adsorb β-carotene optimally. Adsorption of β-carotene at 40 °C for 60 min according to Freundlich models with the intensity of adsorption of 1.002 and adsorption capacity of 63.358 L/mg. While the adsorption of β-carotene at 50 °C for 60 min in accordance with the model of Langmuir, the adsorption capacity of 33.206 mg/g and the Langmuir adsorption equilibrium constant of 1.721 L/mg.